Plant Extract Valorization of Melissa officinalis L. for Agroindustrial Purposes through Their Biochemical Properties and Biological Activities - Mouna Souihi; Rayda Ben Ayed; Imen Trabelsi; Marwa Khammassi; Nadia Ben Brahim; Mohamed Annabi (Journal of Chemistry)
Lemon balm (Melissa officinalis L.) is one of the rare medicinal plants in Tunisia. It was found only in two sites in the north of Tunisia with a small number of plants. The study of germination under the NaCl and PEG effect showed that Tunisian lemon balm seeds were sensitive to saline and osmotic stress. Morphological and biochemical characterizations of Tunisian M. officinalis were performed. Results showed that the Tunisian populations presented plants with long, broad leaves and weak branching. The major constituent in leaf essential oil was germacrene-D with a percentage ranging from 29.17 to 24.6%, and the major fatty acids were polyunsaturated fatty acids, linoleic acid, ranging from 73.93 to 66.74%. The phenolic content of M. officinalis extract varied significantly among origins which could explain the high variation in antiradical scavenging activity. The evaluation of allelopathic activities showed that the extract of the lemon balm leaves presented an allelopathic effect with the majority of the tested seeds.